Lactaptin Induces p53-Independent Cell Death Associated with Features of Apoptosis and Autophagy and Delays Growth of Breast Cancer Cells in Mouse Xenografts - Koval, Olga A. (Public Library of Science, 2014)
Lactaptin, the proteolytic fragment of human milk kappa-casein, induces the death of various cultured cancer cells. The mechanisms leading to cell death after lactaptin treatment have not been well characterized. In this study the in vivo and in vitro effects of a recombinant analogue of lactaptin (RL2) were examined. Following treatment with the recombinant analogue of lactaptin strong caspase -3, -7 activation was detected. As a consequence of caspase activation we observed the appearance of a sub-G1 population of cells with subdiploid DNA content. Dynamic changes in the mRNA and protein levels of apoptosis-related genes were estimated. No statistically reliable differences in p53 mRNA level or protein level were found between control and RL2-treated cells. We observed that RL2 constitutively suppressed bcl-2 mRNA expression and down regulated Bcl-2 protein expression in MDA-MB-231 cells. We demonstrated that RL2 penetrates cancer and non-transformed cells. Identification of the cellular targets of the lactaptin analogue revealed that α/β-tubulin and α-actinin-1 were RL2-bound proteins. As the alteration in cellular viability in response to protein stimulus can be realized not only by way of apoptosis but also by autophagy, we examined the implications of autophagy in RL2-dependent cell death. We also found that RL2 treatment induces LC3-processing, which is a hallmark of autophagy. The autophagy inhibitor chloroquine enhanced RL2 cytotoxicity to MDA-MB-231 cells, indicating the pro-survival effect of RL2-dependent autophagy. The antitumour potential of RL2 was investigated in vivo in mouse xenografts bearing MDA-MB-231 cells. We demonstrated that the recombinant analogue of lactaptin significantly suppressed the growth of solid tumours. Our results indicate that lactaptin could be a new molecule for the development of anticancer drugs.